Pendapat Imam Syafi’i tentang Hak Ijbar Wali: Suatu Kajian Berperspektif Gender - Ayi Ishak Sholih Muchtar; Rd. Zihad; Ita Puspitasari (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
One result of the still limited understanding of the community in understanding the rights of ijbar wali is that the culture of forced marriage is still rooted. Ijbar rights should be interpreted as a form of protection or responsibility of a father towards his child. Because the condition of the child who is considered not yet or does not have the ability to act alone in marriage, it is even understood as a tool to legitimize the actions of parents to force their children to marry or marry their children with their choice, not their children's choice. This is because there are differences in Ulama and Ijbar rights which are also debated especially when faced with contemporary issues such as gender.